Contemporary editing - Friend, Cecilia (McGraw-Hill, 2005)
The book offers comprehensive instruction about news value, ethics, newsroom decision making and an understanding of audience. The text equips students with solid editing skills for effective use in today's world of evolving mediums and news foru,s. The book also mentions on editing for broadcast and the Web.